THE LEARDERSHIP ROLE OF SCHOOL PRINCIPALS IN ONLINE LEARNING DURING THE COVID-19 PANDEMIC - Ainur Rahman; Subiyantoro Subiyantoro (JURNAL AL-TANZIM, 2021)
This study aims to describe and analyze the leadership role of school principals in online learning during the Covid-19 pandemic. This study used a qualitative approach with phenomenology. The research site at SD Negeri Krapyak Wetan. The data collection technique is done through interviews, documentation and observation. Data analysis was carried out through data collection, data reduction and ending with drawing conclusions. The results showed that; the role of the principal's leadership in online learning during the Covid-19 pandemic, is; a) Optimizing learning and deliberations with teachers, b) Providing education and training on online learning platforms (online), c) Providing appreciation and motivation to teachers, students and guardians of students, d) Conducting multidirectional coordination and communication.